Sosialisasi Hukum Syariah Bagi Pegawai Desa Pematang Rahim: Meningkatkan Pemahaman Dan Penerapan Dalam Pelayanan Publik - Dinda Mayang Apriliani; Sri Kadarsih; Wandi; Erwina Kartika Devi; Isna (Gotong Royong, 2025)
Quality and ethical public service is a fundamental pillar for realizing governance that is just, transparent, and oriented toward community welfare. This community service program aims to enhance the understanding and application of sharia legal principles in public service within Pematang Rahim Village, Mendahara Ulu Subdistrict, Tanjung Jabung Timur Regency. The initiative was motivated by the limited understanding of village officials regarding Islamic legal values that should underpin ethical governance practices. The implementation employed a participatory and educational approach through interactive socialization, reflective lectures, and focus group discussions (FGDs) emphasizing the application of the principles of ‘adl (justice), amanah (trustworthiness), and maslahah (public benefit) in public service contexts. The results indicate a significant improvement in participants’ understanding based on pre-test and post-test evaluations, increasing from 57.7% to 87.3% (a rise of 29.6%). The highest improvement occurred in the aspect of public service ethics based on sharia principles (30%), followed by the ability to apply sharia values in governance (30%), and understanding of basic sharia law concepts (29%). Beyond knowledge enhancement, the program fostered collective awareness among village officials, reflected in their initiative to draft the Islamic Public Service Ethics Guidelines as a follow-up action. Thus, this program not only strengthens the intellectual and spiritual capacity of village officials but also represents a strategic step toward establishing a village governance system that is just, transparent, accountable, and grounded in Islamic ethical values.